Strain‐specific quantification of Wolbachia density in subtropical Argentinean Aedes albopictus: effects of tissue location and longevity - Chuchuy, Ailén; Rodriguero, Marcela S.; Micieli, M. Victoria (Frontiers in Insect Science, 2025)
The intracellular bacterium Wolbachia pipientis has emerged as a promising tool for controlling mosquito-borne diseases; however, key aspects of its biology remain insufficiently understood, particularly how Wolbachia influences vector competence for certain arboviruses. The main factors implicated are the activation of mosquito antiviral pathways and competition for cellular resources at the viral replication site. Transinfection of Wolbachia strains into vector populations has proven to be an effective strategy for controlling arboviral diseases. Here, we investigate the within-host density and tissue distribution of two naturally occurring Wolbachia strains—wAlbA and wAlbB—n Aedes albopictus from Argentina, where infection patterns diverge from those observed globally. Using quantitative PCR, we assessed symbiont density in ovarian (n = 5) and somatic tissues (n = 5) of adult females, and in adult males across different ages: 0, 5 and 14 days post-emergence (n = 5 per age group). Our results reveal superinfection in ovaries (wAlbA + wAlbB) with similar densities (median relative densitywAlbA = 3.78 and median relative densitywAlbB = 3.31), but only wAlbB was consistently detected in somatic tissues (median relative densitywAlbB = 0.41), suggesting tissue-specific distribution of strains. Additionally, wAlbB density in males remained stable throughout the adult lifespan (median relative densityTime0 = 0.83; median relative densitytime 5 = 1.98; median relative densitytime 14 = 0.66). These findings support the hypothesis that Wolbachia somatic localization is strain-specific and may be under evolutionary selection, with implications for vertical transmission and host fitness. By advancing our understanding of Wolbachia density dynamics in a natural mosquito vector population, this study contributes critical baseline data to inform and optimize Wolbachia-based biocontrol strategies in regions at risk of arboviral outbreaks. Because the wAlbB strain from Ae. albopictus is widely used in replacement techniques, any knowledge of its behavior in natural host populations is valuable.